Molecular genetic predictors of metastatic lesions of regional lymph nodes in patients with breast cancer - V. V. Rodionov; O. V. Burmenskaya; V. V. Kometova; D. Yu. Trofimov; M. V. Rodionova; L. A. Ashrafyan (Опухоли женской репродуктивной системы, 2021)
Objective: to identify molecular genetic predictors of metastatic spread to regional lymph nodes in patients with breast cancer (BC) based on the analysis of gene expression profile of the primary tumor.Materials and methods. The study included 358 patients with BC who underwent surgical treatment in breast cancer department of Academician V.I. Kulakov Research Center of Obstetrics, Gynecology, and Perinatology, Ministry of Health of Russia. Among all included into the study patients, 132 (36.9 %) had metastases in at least one axillary lymph node. Molecular genetic examination of the tumor tissue was carried out using reverse transcription polymerase chain reaction; the diagnostic panel consisted of 45 functional and 3 reference genes. Results. Patients with metastases to regional lymph nodes were generally younger (p = 0.006), had larger primary tumor (p<0.001) and higher total malignancy score (p<0.001). The groups were also significantly different in tumor location (p = 0.005). Comparative analysis of transcriptome tumor profiling revealed statistically significant differences between groups in the level of expression of three genes: TMEM45A (p = 0.016), CCND1 (p = 0.019), and MIA (p = 0.046). Based on the data obtained we used mathematical modeling and created a predictive model, which with a high degree of probability (AUC = 0.791) allowed to predict the presence of regional lymph nodes metastases in patients with BC.Conclusion. TMEM45A, CCND1 and MIA gene expression in the primary tumor were the markers of lymph node involvement in BC. The developed predictive genetic signature can become an additional diagnostic tool to predict the risk of lymph node metastases at the point of planning the volume of axillary surgery in patients with BC.